Determination of the disinfectants efficiency on microorganisms - active gray rot causative agents within the process of sugar beet storage - Gusyatinska, Natalia; Teterina, Svitlana; Nechypor, Tatiana; Kasian, Irina (My University, 2015)
The article presents the results of research on the effectiveness of modern disinfectants on the basis of sodium salts of dichlorosaccharide, polyhexamethylene guanidine, citroside, monensin sodium and natural hydroxy acids in relation to the contaminating microflora of sugar beets.
Keywords: дезінфікуючі засоби; цукор; мікроміцети; слизоутворюючі бактерії; дезинфицирующие средства; сахар; микромицет; слизеобразующие бактерии; disinfectants; sugar; micromycetes; slime-forming bacteria; кафедра біотехнології і мікробіології; кафедра технології цукру і підготовки води